Conservative management of invasive cervical resorption: a case report. - Fahad Umer; Samira Adnan; Farhan Raza Khan (Tehran University of Medical Sciences, 2013)
Invasive cervical resorption is a condition that affects the root surface area below the epithelial attachment. Multiple treatment modalities are advocated, involving exposure of the invasive defect, removal of the granulation tissue and sealing with various restorative materials. This report demonstrates conservative treatment of a patient presenting with peri-apical periodontitis in upper right central and lateral incisors, along with Class II invasive resorption defect cervically on the mesial aspect of the central incisor, as a result of trauma. As the patient was not willing for any surgical intervention, only ortho-grade root canal treatment was carried out in both teeth, with Calcium hydroxide as intra-canal medicament. At three year follow-up, the patient remains asymptomatic demonstrating radiographic evidence of infilling of defect with bone-like tissue. Within the limitations of this report, it was seen that this conservative method for halting the progression of invasive cervical resorption could be under taken in patients who are un-willing for surgical intervention or in whom surgery is contra-indicated.